Tectonic Evolution of the Bering Shelf-Chukchi Sea-Artic Margin and Adjacent Landmasses 2002
DOI: 10.1130/0-8137-2360-4.167
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crust and mantle beneath the Bering Sea region: Evidence from xenoliths and late Cenozoic basalts

Abstract: Late Cenozoic volcanic centers throughout the Bering Sea region of Alaska consist of small-volume eruptions of ×ows and cones of tholeiitic to alkaline basalt. Peridotite (spinel lherzolite, websterite, wehrlite, and pyroxenite) and gabbro xenoliths are abundant in some of the most alkaline ×ows and cones. Spinel lherzolite xenoliths are characterized by granuloblastic-equant and coarse-equant textures typical of mantle peridotites and yield equilibration temperatures of 1000-1200 °C (1.5 GPa). Relative to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…We demonstrate the compatibility of our model with Cenozoic Arctic Ocean opening along the Gakkel Ridge, and also the consistency between inferred Siberia-Alaska convergence with transpressive right-lateral tectonics of the Brooks Range in Arctic Alaska (e.g. Wirth et al, 2002;Golonka et al, 2003). far as northern Alaska.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We demonstrate the compatibility of our model with Cenozoic Arctic Ocean opening along the Gakkel Ridge, and also the consistency between inferred Siberia-Alaska convergence with transpressive right-lateral tectonics of the Brooks Range in Arctic Alaska (e.g. Wirth et al, 2002;Golonka et al, 2003). far as northern Alaska.…”
Section: Discussionsupporting
confidence: 59%
“…This convergence appears to be oblique between the Chukotka subplate (Golonka et al, 2003;Fig this range (e.g. Wirth et al, 2002;Golonka et al, 2003), and (2) the Cenozoic transpressive deformation along the Moma rift system (e.g. Gaina et al, 2002).…”
Section: Arctic Constraintsmentioning
confidence: 95%
“…The Kaltag and the Fairweather faults postdate the era of terrane accretion, which was mostly middle Cretaceous in the area of these faults (Klemperer et al, 2002a). Many of the volcanic centers in western Alaska occur near the ends of the surface expressions of major strike-slip faults or along their projected traces (Wirth et al, 2002); for example, Figure 1 shows the Quaternary Togiak basalt field at the western terminus of the Denali Fault and the Saint Michael volcanic field near the end of the Kaltag Fault. The Denali fault system extends ~1500 km from western Canada to near the edge of the Bering Sea.…”
Section: Major Strike-slip Faultsmentioning
confidence: 99%
“…Major onshore strike-slip faults (e.g. Denali and Tintina) whose orientation varies from southeast to southwest (Wirth et al, 2002) can be clearly identified on geological maps of southwestern Alaska. Though several models (Cross and Freymuller, 2008;Finzel (2011)) of Alaskan evolution have been proposed, it remains uncertain whether these faults (1) extend offshore across the entire Bering shelf from northeast to southwest, (2) rotate to form a trend parallel to the shelf edge, or (3) terminate under the inner Bering shelf.…”
Section: Introductionmentioning
confidence: 99%